ChemInform Abstract: An Umpolung Approach Toward N‐Aryl Nitrone Construction: A Phosphine‐Mediated Addition of 1, 2‐Dicarbonyls to Nitroso Electrophiles. Issue 7 (29th January 2015) - Chavannavar, Aditi P.; Oliver, Allen G.; Ashfeld, Brandon L.
Abstract A complementary approach toward nitrone construction that circumvents a conventional condensation strategy by exploiting the unusual reactivity of 1, 2‐dicarbonyls with phosphines is reported.